2008
DOI: 10.1016/j.jacc.2008.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Plasma N-Terminal B-Type Natriuretic Peptide as an Indicator of Long-Term Survival After Acute Myocardial Infarction: Comparison With Plasma Midregional Pro-Atrial Natriuretic Peptide

Abstract: The A- and B-type natriuretic systems are activated after AMI. Midregional pro-atrial natriuretic peptide is a powerful predictor of adverse outcome, especially in those with an elevated NT-proBNP. Midregional pro-atrial natriuretic peptide may represent a clinically useful marker of prognosis after an AMI as part of a multimarker strategy targeting the natriuretic neurohormonal pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…19 N-terminal B-type natriuretic peptide (NT-BNP) was measured using the Dimension RxL N-BNP (Dade-Behring, Germany). 20 …”
Section: Baseline Examinationsmentioning
confidence: 99%
“…19 N-terminal B-type natriuretic peptide (NT-BNP) was measured using the Dimension RxL N-BNP (Dade-Behring, Germany). 20 …”
Section: Baseline Examinationsmentioning
confidence: 99%
“…Two studies assessed the prognostic value for all-cause mortality, one in patients with chronic heart failure (14 ) and another in patients after an acute myocardial infarction (15 ). One study compared the 2 peptides with respect to diagnosing heart failure (16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The difference became significant at 48 months, with areas under the ROC curve of 0.79 and 0.75 for MR-proANP and NT-proBNP, respectively (P ϭ 0.03). The other 2 studies observed no differences between the 2 peptides (15,16 ). Whereas these 3 studies performed ROC curve analyses, we used Harrell C statistics.…”
Section: Resultsmentioning
confidence: 99%
“…19 Besides BNP and NTproBNP, the newly introduced midregional pro-atrial natriuretic peptide (MRproANP), a fragment of N-terminal pro atrial natriuretic peptide (NT-proANP), had its prognostic value assessed in a recently published study in 983 patients with acute myocardial infarction (the Leicester Acute Myocardial Infarction Peptide [LAMP] study). 20 MRproANP was independently associated with mortality and provided additional prognostic information to NTproBNP, as it identified those patients with more adverse outcome in the highest NTproBNP quartile.…”
Section: Prognostic Value Of Natriuretic Peptides In Acsmentioning
confidence: 94%
“…In a subanalysis of the Prevention of Events With Angiotensin-Converting Enzyme Inhibition (PEACE) trial, which evaluated the prognostic value of baseline BNP and NTproBNP levels in 3761 patients with low-risk, stable coronary artery disease and preserved left ventricular function, 21 BNP was an independent predictor of an increased risk of heart failure development, while NTproBNP was independently 8,11,15,17,19,20,29 Non-ST-elevation myocardial infarction [11][12][13][14][15]17,20,27,29,32 Acute coronary syndrome in the absence of detectable myocardial necrosis (unstable angina) 9,12,13,15,27,29,32 Uncomplicated percutaneous coronary intervention in the presence of stable intracardiac filling pressure 12,16 Stable coronary artery disease 6,[21][22][23][24][25][26][28][29][30] natriuretic peptides in ACS july . august 2008 .…”
Section: Prognostic Value Of Natriuretic Peptides In Stable Coronary mentioning
confidence: 99%